P273 Inflammatory Bowel Disease and COVID-19 vaccine. (21st January 2022) - Zahra Bianco, E; Tabone, T; Cassar, P; Agius, D; Zammit, D; Vella Baldacchino, A; Scicluna, C; Gatt, K; Ciantar, M; Montebello, B; Ellul, P; Sciberras, M
Abstract: Background: Owing to the COVID-19 pandemic, inflammatory bowel disease (IBD) patients are strongly encouraged to vaccinate against SARS-COVID-19. In fact, the uptake of this vaccine in IBD cohorts has been greater than the general population. The adverse events of this vaccine are predicted to be low. The aim of this study was to assess the percentage of IBD patients who took the COVID-19 vaccine- including booster- and any significant adverse events. Any possible correlation with lifestyle habits, treatment and disease activity was also established. Methods: Data was collected prospectively. 200 patients with a histological diagnosis of IBD were randomly recruited through our local database. Data was gathered using electronic case summaries and direct patient contact. Data collected included; diagnosis, type and number of COVID-19 vaccines taken, demographics, lifestyle habits, treatment and any adverse events to the vaccine. Patients were also asked about any concerns regarding this vaccine. Results: 187 patients (57.8% male) were recruited. 73.8% of which had Crohn's disease (CD), 25.7% had Ulcerative colitis (UC) and 0.5% were unclassified. Mean age was 41.96 (SD ±16.56). 37.8% were on Azathioprine/6- Mercaptopurine, 93.5% were on biologicals and 33.2% were on both. 61% had quiescent IBD while 2.1% had severe IBD. 19.7% were current smokers while 15.8% were ex-smokers. 98.9% received at least one COVID-19 vaccine. Table 1 illustrates the type of vaccine administered to IBD patients. 17% of patients were concerned regarding the effectiveness of the vaccine due to IBD treatment. 19.8% of IBD patients believed that the vaccine may trigger a flareup of their disease. 11.8% of patients felt that not enough information was available to make an informed choice. 7.1% of IBD patients had treatment altered in response to the COVID-19 vaccine. Graph 1 shows the percentage of both local and systemic adverse events to 1 st, 2 nd and 3 rd Covid-19 vaccine in IBD patients. Conclusion: This study demonstrates that the uptake of COVID-19 vaccine in IBD patients was high. The most commonly report adverse events were pain at the injection site and fever. Increased in temperature at the injection site occurred more frequently with the 3 rd dose. A number of patients had a change in their medication in response to at least one the vaccines. Larger studies are needed to decipher whether data can be extrapolated on a larger scale.